The First Case of Bovine Astrovirus-Associated Encephalitis in the Southern Hemisphere (Uruguay), Uncovers Evidence of Viral Introduction to the Americas From Europe - Giannitti, Federico; Caffarena, Rubén Darío; Pesavento, Patricia; Uzal, Francisco Alejandro; Maya, Leticia; Fraga, Martín; Colina, Rodney; Castells, Matías (Frontiers in Microbiology, 2019)
Astrovirus species members of the Mamastrovirus genus (family Astroviridae) have been increasingly recognized as neuroinvasive pathogens in various mammals, including humans, mink, cattle, sheep, and pigs. While cases of astrovirus-associated encephalitis have been reported in North America, Europe and Asia, their presence has never been documented in the Southern hemisphere. This paper describes a case of astrovirus-associated encephalitis in cattle in Uruguay that broadens the geographic distribution and genetic diversity of neuroinvasive astroviruses and provides phylogeographic evidence of viral introduction to the Americas from Europe. A 22-month-old Holstein steer from a farm in Colonia department, Uruguay developed progressive neurological signs over a 3-day period before dying. Histopathological examination of the brain and proximal cervical spinal cord revealed disseminated, moderate to severe lymphocytic, histiocytic and plasmacytic poliomeningoencephalomyelitis with neuronal necrosis. A Mamastrovirus strain in the CH13/NeuroS1 clade we called bovine astrovirus (BoAstV)-Neuro-Uy was identified by reverse transcriptase PCR followed by nearly complete genome sequencing. Additionally, BoAstV was detected intralesionally in the brain by chromogenic RNA in situ hybridization within neuronal perikarya, axons and dendrites. Phylogenetic analysis of BoAstV-Neuro-Uy revealed a close relationship to neurotropic BoAstVs within the Virginia/Human-Mink-Ovine clade, which contains a growing cadre of neuroinvasive astroviruses. Analyzing the complete coding region of neuroinvasive BoAstVs sequences available in GenBank, we estimated an evolutionary rate of 4.27x10-4 (95% HPD 2.19–6.46x10-4) nucleotide substitutions/site/year. Phylogeographic analysis suggests that the common viral ancestor circulated in Europe between 1794-1940, and was introduced in Uruguay between 1849-1967, to later spread to North America and Japan.